Transformations of Digital Culture in Doctoral Studies in Pedagogy: Case of the University of Latvia - Rubene, Zanda; Strods, Raimonds (Acta Paedagogica Vilnensia, 2017)
Quality assurance within higher education studies, in the context of challenges associated with digital culture, requires scientific analysis. The legislation of Latvia predetermines that higher education institutions, being autonomous education and research institutions, are responsible for the quality of education delivered in Latvian higher education establishments. The hierarchic analysis of the most important development and planning documents of Latvia allows to conclude that the digitalization of the higher education area bears only a permissive character; however, the assurance of education quality nowadays is impossible without meaningful integration of ICT in the study process. The research conducted by the European Association of Universities on the transformations of higher education area in the context of digitalization has led to the conclusions that the development of digitalization strategies within the European higher education area has not been put forward as a national level issue remaining the responsibility of the education institutions themselves. Therefore, it is crucial to explore how the changes caused by digitalization are implemented in the concrete study programs. It is particularly important to explore the quality of higher education programs, as the programs within this education cycle comprise both education and research, illustrating the essence of the higher education institution as an autonomous education and research institution. The study, by applying the discourse analysis as a research method, aimed to assess the doctoral program of pedagogy, implemented by the University of Latvia, in order to find out how the discourse characterizing the digitalization of higher education is revealed in the annual self-evaluation reports of the programme.